Saad Zaghlul and Egyptian nationalism - Bearce, George Donham, 1922-1965 (My University, 1949)
Contents include: the birth of Egyptian nationalism, nationalism quiet, nationalism reborn 1906-1908, nationalism suppressed 1908-1911, legislative changes and disillusionment 1913-1914, the war of 1914 and Egyptian nationalism, the rise of Saad Zaghlul to power, the revolution of protest, Zaghlul and the boycott of the Milner Mission, Zaghlul's negotiations with Lord Milner, Zaghlul's struggle with Adly Pasha, the Battle of the petitions, and Saad Zaghlul's second exile.
7 p.l., 234, [10] leaves ; 29 cm.